Impact of the amount of preoperative erector spinae muscle in stage I non-small-cell lung cancer. (31st October 2022) - Ueda, Daisuke; Tsutani, Yasuhiro; Kamigaichi, Atsushi; Kawamoto, Nobutaka; Tsubokawa, Norifumi; Ito, Masaoki; Mimae, Takahiro; Miyata, Yoshihiro; Okada, Morihito
Abstract: OBJECTIVES: Erector spinae muscle (ESM) is an antigravity muscle group that can be evaluated as an index of muscle loss on chest computed tomography. The amount of ESM has been reported to be related to the prognosis of several respiratory diseases. However, few studies clarify the impact on postoperative non-small-cell lung cancer (NSCLC). We investigated the relationship between ESM and postoperative prognosis in patients with early-stage NSCLC. METHODS: We reviewed the medical records of 534 patients with stage I NSCLC who underwent lobectomy or segmentectomy. The ESM was identified by preoperative computed tomography, and the amount was normalized according to height and sex. Overall survival, lung cancer-related deaths and non-lung cancer-related deaths (NLCRD) were analysed using log-rank and Gray's tests. Multivariable analyses were conducted to identify factors that influenced overall survival (OS) and NLCRD. RESULTS: The amount of ESM normalized according to height and sex was significantly associated with age and body mass index. When the amount was low, OS (5-year OS, 79.6 vs 89.5%; P < 0.001) and NLCRD (5-year cumulative mortality rate, 14.7 vs 6.8%; P < 0.001) were significantly worse, although no difference was found in lung cancer-related deaths. CONCLUSIONS: The amount of preoperative ESM was strongly related to non-lung cancer-related death and was a significant prognostic factor for stage I NSCLC. Patients with a low amount of the muscle should be treated based on proper risk assessment. Abstract : Patients with lung cancer experience one of the lowest 5-year survival rates [1].